DEVELOPMENT OF THE TEXTUAL COMMUNICATIVE COMPETENCES IN POSTGRADUATE STUDENTS - Zhizhko, Elena (Studies in Comparative Education, 2018)
In this article we present the results of the documentary-bibliographic study, which goal was to determine, what strategies for the development in the students of textual communicative competences are available to the teacher in a social sciences and humanities postgraduate programs. The research was carried out from the focus on communicative competence. From the analysis made, it can be affirmed that for the successful development in postgraduate students of textual communicative com-petences, the teacher must take into account that their acquisition involves the mas-tery of the complex and specialized (scientific-academic) discursive style; it foresees obligatory appropriation of other communicative competences: linguistics, pragma-tic, paralinguistic, strategic, descriptive referential, representative, organizational, illocutionary; their teaching requires careful preparation: selection of the functional style of the language as a means of scientific communication and articulation around it of different forms of effective and practical learning; choice of didactic texts; coordination of reading and writing teaching actions; elaboration of the exer-cises of interpretation, paraphrase, commentary, annotations, recapitulation, limi-tation, description of the content, conceptual map, compendium-summary, etc.